(3GdWQGR GdehTi aj GdGfTGAs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3fSNI cJGH hQO Ydi GdGHhGH GdTQjaI GdedcjI ef GdTjN HQgGf GdOjf GdHGZhfi GdTGaYi jbHd GdGQV GdJi jhO dh XaQ HbQHgG hjSCd Gddg LdJ fYeGhg s
(3BNQgG (B:s
(3aJbYO ePehekG eOMhQG Ef gPg JPcQI aef TGA GJNP Edi QHg SHjdG hGddg JYGdi jLYd eG QSefG Hg ef Pdc NGdUkG dhLgg GdcQje hGdMeO ddg QH GdYGdejf Je GdWQGR GdehTi ai GdGfTGA s
(3eUOQ GbJfGA GdCUd (B:s
(3SgdGQ (B(785/2795) s
Keywords: (3GdCOHs